Analysis of Oversize of Engine Compressor Disk. (October 2019) - Zhang, Lili; Zhao, Yuan; Tao, Lin; Liu, Yefeng; Yang, Yufang
Abstract: In order to solve the problem of the extreme axial position of the engine compressor during the process of machining, three kinds of calculation States were selected according to the extreme difference, and the influence of the excess on the stress and deformation of the compressor was determined.